eparation of Close Boiling Acidic Isomers by Dissociation Extraction (Biological Sciences - PJSIR, 2005)
The separation of m-cresol and p- cresol was studied using dissociation extraction technique. The separation factors obtained for cresols-carbon tetrachloride-caustic soda system were in the range of 1.40 to 1.52, whereas for cresolscarbon tetrachloride-monoethanolamine system were in the range of 1.297 to 1.417. Isomer ratios, concentration of cresols and the strength of aqueous extractant have a significant influence on the separation of cresols. The organic acid (m- cresol ) was successfully back-extracted from aqueous caustic soda with a non-polar organic solvent, octanol. pH of the aqueous phase and the choice of organic solvent have an important role in the back-extraction of m- cresol.